Comparative Outcomes of Balloon Sinuplasty versus Functional Endoscopic Sinus Surgery (Fess) In Chronic Rhinosinusitis without Polyps - Dr. Srikanth Reddy Barla; Dr. Bodagala Himahashini (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Chronic rhinosinusitis without nasal polyps (CRSsNP) represents a prevalent inflammatory disorder of the paranasal sinuses characterized by persistent mucosal inflammation, nasal obstruction, and impaired quality of life. Functional endoscopic sinus surgery (FESS) remains the gold standard for surgical management when maximal medical therapy fails. However, balloon sinuplasty, a minimally invasive alternative, has gained popularity for its tissue-sparing technique and faster recovery. Comparative data assessing both interventions in CRSsNP remain limited. Methods: A comparative cohort study was designed to evaluate outcomes of balloon sinuplasty and FESS in adult patients with CRSsNP refractory to optimal medical management. Two important measures were the improvement of symptoms as assessed using Sinonasal Outcome Test (SNOT-22) and change on radiological imaging based on Lund-Mackay CT score. Other outcome measures were operative time, intraoperative hemorrhage, complication rates, and postoperative recovery as well as revision rates. Results: Both interventions produced a notable reduction in a symptom score and a radiologic parameter after the 12 months follow-up period. Balloon sinuplasty was proven to have less operative times, less intraoperative blood loss, and earlier resumption of normal activity. Although the recovery process is longer when using FESS, it was associated with better results in patients who have an increased preoperative burden of disease and surgical complexity. There were minimal but insignificant differences in the rates of revision surgery which were higher in the balloon group. Conclusion: Balloon sinuplasty and FESS are helpful in the treatment of CRSsNP. Balloon sinuplasty is less invasive, safer and with faster recovery period compared to FESS, which is more beneficial when the disease is advanced. Good patient selection is of necessity to maximize the result.